PANDANGAN NAHDLATUL ULAMA TENTANG STATUS WARGA NEGARA NON-MUSLIM DI INDONESIA - Hermawan, Rahmat; Kurniati; Asni (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
Abstract This study aims to determine the analysis of the status of non-muslim citizens according to Nahdlatul Ulama’s view, and to try find the relevance of non-muslim citizens according to Nahdlatul Ulama to the implementation of the political rights of citizens in Indonesia. This research is library research, with a theological-normative, syar’i and historical approach. The fiqh concerning citizens initiated by the jurists places the position of non-muslims (infidel) dzimmih, mu’ahad, musta’man and harbi being irrelevant to the concept of the nation state. It can be seen that in accoardance with the socio-cultural and political conditions of the nation in Indonesia, it is not included in the category of darul Islam and darul harbi. The application of the nation-state concept, placing all citizens equally before the law without any background tendencies. The reappearance of the labeling of citizens based on religious backgrounds in political contestations has made Nahdaltul Ulama seek to re-knit the threads that have been tangled up due to indetity politics in the name of religion, returning to the full meaning of citizens according to the 1945 Constitution of the Republic of Indonesia.